Impact of professional experience on clinical judgment and muscular response in various neuromuscular tests - Rey-Mota, Jorge; Escribano-Colmena, Guillermo; Fernández-Lucas, Jesús; Parraca, Jose A.; Clemente-Suárez, Vicente Javier (Physiology & behavior, 2024)
•We aimed to identify an objective evaluation system sensitive to analyze changes in different muscular conditions in different neuromuscular tests.•Digital dynamometry was identified as the most sensitive tool for detecting changes in neuromuscular tests.•Significant differences were found in objective parameters and clinical judgment between practitioners of different expertise levels.•Higher expertise participant presented a clinical judgment like digital dynamometer. Muscle testing is an integral component in assessing musculoskeletal function and tailoring rehabilitation efforts. This study aimed i. to identify an objective evaluation system sensitive to analyze changes in different muscular conditions in different neuromuscular tests across a spectrum of professional experience levels; and ii. to analyze differences in objective parameters and clinical judgment between participants of different levels of expertise in different muscular conditions in different neuromuscular tests. Participants included 60 subjects with Level I to III expertise who performed blinded neuromuscular tests on the middle deltoid and rectus femoris muscles of 40 volunteer subjects. The methodology centered on standardizing test protocols to minimize variability, employing EMG to quantify muscle activity, thermography to capture thermographic muscular response, and digital dynamometry to measure muscular resistance. The findings revealed that while traditional methods like thermography and electromyography provide valuable insights, digital dynamometry stands out for its sensitivity in detecting muscle condition changes in neuromuscular test. Moreover, the data underscored the pivotal role of advanced training and expertise in enhancing the precision and accuracy of neuromuscular diagnostics, since there were significant differences in objective parameters and clinical judgment between participants of different levels of expertise in the different muscular conditions in Middle deltoid and Rectus femoris neuromuscular tests analyzed, presenting higher expertise participant clinical judgment like objective validated instrument.